Ketimpangan Distribusi Minyak Goreng: Antara Korupsi Ekspor dan Lemahnya Regulasi - Asep Iwan Ridwan Nugraha; Halimah Zahrah; Muhammad Raihan N. M; Rayhan Azhari Ilham (Teewan Journal Solutions, 2025)
This research examines corruption practices within Indonesia's crude palm oil (CPO) export trade, which have led to scarcity and price hikes in the domestic cooking oil market. The main problem is the disparity between the abundant domestic supply of CPO and the shortage of cooking oil for consumers, indicating fraudulent and corrupt practices within the supply chain and export policies. The aim of this study is to analyze the forms of corruption occurring, identify weaknesses in the regulatory framework and oversight of CPO export trade, and formulate strategies for prosecuting corporate offenders and recommending improvements to the trade system. Using a qualitative research methodology with a case study approach on the cooking oil export corruption case, data were collected through document analysis, interviews, and policy analysis. The research findings indicate that corruption manifests through abuse of authority in granting export permits (export approvals and Domestic Market Obligation/DMO), manipulation of export volume data, and collusion between officials and corporations. Regulatory and oversight weaknesses, including the sub-optimal prosecution of corporations as legal subjects, also contribute to the problem. The recommendations include strengthening regulations on corporate liability for corruption, enhancing transparency and accountability in the export licensing system, and a comprehensive reform of the cooking oil trade system to ensure domestic availability and price stability.